Tobacco cessation in India: A contemporary issue in public health dentistry - Ramya Kalyanpur; K Pushpanjali; KVV Prasad; Kumar Gaurav Chhabra (Wolters Kluwer Medknow Publications, 2012)
In India, tobacco use is incredibly linked to poverty and accounts for the high public health costs of treating tobacco-related diseases. Dental public health programs aid in detecting the tobacco-related periodontal diseases, oral cancers, etc., where the majority belongs to the submerged portion of iceberg, which otherwise leads to substantial morbidity and mortality. Moreover, public health dentists plays a key role in identifying both clinical and subclinical cases and aid in tobacco use cessation through various modes of health education and counseling. Therefore, the community-based measures are deemed to be the most cost-effective tool for tobacco cessation.